2013
DOI: 10.1186/1471-2148-13-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of complete mitochondrial genome sequences confirms independent origins of plant-parasitic nematodes

Abstract: BackgroundThe nematode infraorder Tylenchomorpha (Class Chromadorea) includes plant parasites that are of agricultural and economic importance, as well as insect-associates and fungal feeding species. Among tylenchomorph plant parasites, members of the superfamily Tylenchoidea, such as root-knot nematodes, have great impact on agriculture. Of the five superfamilies within Tylenchomorpha, one (Aphelenchoidea) includes mainly fungal-feeding species, but also some damaging plant pathogens, including certain Bursa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 47 publications
(75 reference statements)
11
65
0
Order By: Relevance
“…Some studies indicated that Ascarididae was more closely related to the Toxocaridae than to Anisakidae by molecular criteria (Nadler and Hudspeth, 1998;Nadler et al, 2007;Li et al, 2008b;Xie et al, 2011a), but were rejected by analyses using small subunit (SSU) and mt genome sequences (Blaxter et al, 1998;Meldal et al, 2007;Park et al, 2011;Sultana et al, 2013). The results of the present study supports that the Ascarididae was more closely related to the family Toxocaridae than to other families within the Ascaridomorpha, consistent with findings of a recent study (Liu et al, 2013b).…”
Section: Discussionsupporting
confidence: 82%
“…Some studies indicated that Ascarididae was more closely related to the Toxocaridae than to Anisakidae by molecular criteria (Nadler and Hudspeth, 1998;Nadler et al, 2007;Li et al, 2008b;Xie et al, 2011a), but were rejected by analyses using small subunit (SSU) and mt genome sequences (Blaxter et al, 1998;Meldal et al, 2007;Park et al, 2011;Sultana et al, 2013). The results of the present study supports that the Ascarididae was more closely related to the family Toxocaridae than to other families within the Ascaridomorpha, consistent with findings of a recent study (Liu et al, 2013b).…”
Section: Discussionsupporting
confidence: 82%
“…Using mt genes, Park et al (2011) found that Ascaridida, Oxyurida and Spirurida did not share a most recent common ancestor, which does not support the monophyly of Clade III. Furthermore, Sultana et al (2013b) demonstrated that B. xylophilus was not closely related to members of Tylenchoidea (Heterodera, Pratylenchus and Radopholus), confirming the independent origins of PPNs. In a recent study, Humphreys-Pereira and Elling (2014) used 12 mt PCGs to confirm the convergent evolution of sedentary endoparasitism in Meloidogyne and Heterodera.…”
Section: Introductionmentioning
confidence: 72%
“…At the time of this study (October 2014), there are 11 mt genomes of PPNs published, i.e., M. chitwoodi, M. incognita, Meloidogyne graminicola, Heterodera glycines, Globodera pallida, Globodera rostochiensis, Pratylenchus vulnus, R. similis, B. xylophilus, Bursaphelenchus mucronatus and Xiphinema americanum (Armstrong et al, 2000;He et al, 2005;Gibson et al, 2007Gibson et al, , 2011Jacob et al, 2009;Sultana et al, 2013aSultana et al, , 2013bSun et al, 2014;Besnard et al, 2014). It is likely that the development of new sequencing technologies will accelerate and improve the sequencing of more nematode mt genomes, e.g., Zasada et al (2014) describe the use of Illumina HTS for sequencing the mt genome of single individuals of X. americanum from 12 populations.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the COX3 termination codon (TAA) present in the recently reported mtDNA from a South Korean isolate [GQ332424 (Sultana et al, 2013)] is absent from the Portuguese isolates because of the deletion of a single base ( Figure 1A). The same deletion was observed in the partial mtDNA of a Japanese isolate identified in a BLAST search against B. xylophilus contigs available at http://www.genedb.org/ Homepage/Bxylophilus (Kikuchi et al, 2011).…”
mentioning
confidence: 86%